The research progress of anti-inflammatory and anti-fibrosis treatment of chronic pancreatitis - Li, Bing-Qing; Liu, Xin-Yuan; Mao, Tao; Zheng, Tao-Hua; Zhang, Peng; Zhang, Qi; Zhang, Yu; Li, Xiao-Yu (Frontiers in Oncology, 2022)
Chronic pancreatitis (CP) is a chronic progressive inflammatory disease of the pancreas, caused by multiple factors and accompanied by irreversible impairment of pancreatic internal and external secretory functions. Pathologically, atrophy of the pancreatic acini, tissue fibrosis or calcification, focal edema, inflammation, and necrosis are observed. Clinical manifestations include recurrent or persistent abdominal pain, diarrhea, emaciation, and diabetes. The disease course is prolonged and the clinical prognosis is poor. Currently, clinical treatment of CP is still based on symptomatic treatment and there is a lack of effective etiological treatment. Encouragingly, experiments have shown that a variety of active substances have great potential in the etiological treatment of chronic pancreatitis. In this paper, we will review the pathogenesis of CP, as well as the research progress on anti-inflammatory and anti-fibrotic therapies, which will provide new ideas for the development of subsequent clinical studies and formulation of effective treatment programs.